Sex differences in sleep apnea and Alzheimer’s Disease: role of cerebrovascular dysfunction - Ian M. Greenlund; Jill N. Barnes; Sarah E. Baker; Virend K. Somers; Joshua M. Bock (npj Women's Health)
Abstract Obstructive sleep apnea (OSA) significantly impacts cardiovascular health in post-menopausal females. Given that cardiovascular and cerebrovascular diseases are tightly linked, OSA-mediated impacts on cerebrovascular function and Alzheimer’s Disease (AD) risk are also likely more manifest in females. This review will: summarize sex differences in cerebrovascular function, review the vascular hypothesis of AD, characterize sex differences in the OSA phenotype and implications for cerebrovascular control, and highlight OSA-mediated AD risk.